PENGARUH PROGRAM BLOCK GRANT KECAKAPAN HIDUP TERHADAP HASIL BELAJAR BAHASA INGGRIS - Nurdin Ibrahim (Perspektif Ilmu Pendidikan, 2008)
The aim of this study is to examine the differences in learning achievement in English between the students who receives Block Grant and who don’t. This study was conducted in 2005 at Jakarta Public Senior Highschools which received Block Grant Welfare Program and Jakarta Public Senior Highschools which didn’t receive Block Grant Welfare Program in 2003, located in East, Central, and North Jakarta. This study used Analysis of Variance (ANOVA) with additional approach Tuckey Test at á=0,05, and used expost facto and a 2x2 factorial design. The result of hypotheses testing shows that: first, in overall, there is a significant difference found between English achievement of student who received Block Grant and who didn’t receive Block Grant. Second, there is an interaction between enteryng behaviors and Block Grant Welfare Program to the students’ achievement in English.